Effects of Prenatal Multiple Micronutrient Supplementation on Fetal Growth Factors: A Cluster-Randomized, Controlled Trial in Rural Bangladesh - Gernand, Alison D. (PLoS One, 2015)
Prenatal multiple micronutrient (MM) supplementation improves birth weight through increased fetal growth and gestational age, but whether maternal or fetal growth factors are involved is unclear. Our objective was to examine the effect of prenatal MM supplementation on intrauterine growth factors and the associations between growth factors and birth outcomes in a rural setting in Bangladesh. In a double-blind, cluster-randomized, controlled trial of MM vs. iron and folic acid (IFA) supplementation, we measured placental growth hormone (PGH) at 10 weeks and PGH and human placental lactogen (hPL) at 32 weeks gestation in maternal plasma (n = 396) and insulin, insulin-like growth factor-1 (IGF-1), and IGF binding protein-1 (IGFBP-1) in cord plasma (n = 325). Birth size and gestational age were also assessed. Early pregnancy mean (SD) BMI was 19.5 (2.4) kg/m(2) and birth weight was 2.68 (0.41) kg. There was no effect of MM on concentrations of maternal hPL or PGH, or cord insulin, IGF-1, or IGFBP-1. However, among pregnancies of female offspring, hPL concentration was higher by 1.1 mg/L in the third trimester (95% CI: 0.2, 2.0 mg/L; p = 0.09 for interaction); and among women with height <145 cm, insulin was higher by 59% (95% CI: 3, 115%; p = 0.05 for interaction) in the MM vs. IFA group. Maternal hPL and cord blood insulin and IGF-1 were positively, and IGFBP-1 was negatively, associated with birth weight z score and other measures of birth size (all p<0.05). IGF-1 was inversely associated with gestational age (p<0.05), but other growth factors were not associated with gestational age or preterm birth. Prenatal MM supplementation had no overall impact on intrauterine growth factors. MM supplementation altered some growth factors differentially by maternal early pregnancy nutritional status and sex of the offspring, but this should be examined in other studies. TRIAL REGISTRATION: ClinicalTrials.gov NCT00860470